Pemanfaatan Web Blog sebagai Media Distribusi Informasi Pariwisata - Dewi Yanti (Jurnal Darma Agung, 2018)
This Research explains how to use the web blog as a media for distributing tourism information in helping the learning process of tourism information systems. A case study of designing a web blog to explain this research is in the tourist area of Dairi Regency, North Sumatra province which is the area around Lake Toba which has considerable tourism potential. By utilizing information technology, especially web blogs as a media for information distribution, students feel very effective in terms of processing time and the small costs incurred and the delivery of information can be done quickly and accurately. The potential elements of tourism objects, history, cultural arts, and facilities in designing web blogs are important considerations in this study.